Dietary intervention as a therapeutic for cancer. Issue 2 (31st December 2020) - Morita, Mami; Kudo, Kei; Shima, Hiroshi; Tanuma, Nobuhiro
Abstract: Cancer metabolism is influenced by availability of nutrients in the microenvironment and can to some extent be manipulated by dietary modifications that target oncogenic metabolism. As yet, few dietary interventions have been scientifically proven to mitigate disease progression or enhance any other kind of therapy in human cancer. However, recent advances in the understanding of cancer metabolism enable us to predict or devise effective dietary interventions that might antagonize tumor growth. In fact, evidence emerging from preclinical models suggests that appropriate combinations of specific cancer therapies with dietary interventions could critically impact therapeutic efficacy. Here, we review the potential benefits of precision nutrition approaches in augmenting the efficacy of cancer treatment. Abstract : Recent advances in the understanding of cancer metabolism enable us to predict or devise effective dietary interventions that might antagonize tumor growth. In fact, evidence emerging from preclinical models suggests that appropriate combinations of specific cancer therapies with dietary interventions could critically impact therapeutic efficacy.